The contribution of recombination to heterozygosity differs among plant evolutionary lineages and life-forms - Jaramillo-Correa, Juan P (BioMed Central, 2010)
BACKGROUND: Despite its role as a generator of haplotypic variation, little is known about how the rates of recombination evolve across taxa. Recombination is a very labile force, susceptible to evolutionary and life trait related processes, which have also been correlated with general levels of genetic diversity. For example, in plants, it has been shown that long-lived outcrossing taxa, such as trees, have higher heterozygosity (H(e)) at SSRs and allozymes than selfing or annual species. However, some of these tree taxa have surprisingly low levels of nucleotide diversity at the DNA sequence level, which points to recombination as a potential generator of genetic diversity in these organisms. In this study, we examine how genome-wide and within-gene rates of recombination evolve across plant taxa, determine whether such rates are influenced by the life-form adopted by species, and evaluate if higher genome-wide rates of recombination translate into higher H(e )values, especially in trees. RESULTS: Estimates of genome-wide (cM/Mb) recombination rates from 81 higher plants showed a significant phylogenetic signal. The use of different comparative phylogenetic models demonstrated that there is a positive correlation between recombination rate and H(e )(0.83 ± 0.29), and that trees have higher rates of genome-wide recombination than short-lived herbs and shrubs. A significant taxonomic component was further made evident by our models, as conifers exhibited lower recombination rates than angiosperms. This trend was also found at the within-gene level. CONCLUSIONS: Altogether, our results illustrate how both common ancestry and life-history traits have to be taken into account for understanding the evolution of genetic diversity and genomic rates of recombination across plant species, and highlight the relevance of species life forms to explain general levels of diversity and recombination.